Keeping It Real: How Perceived Brand Authenticity Affects Product Perceptions - Cinelli, Melissa D.; LeBoeuf, Robyn A. (Journal of Consumer Psychology, 2020)
This article examines the effects of firm motivation (an intrinsic or extrinsic interest in their product) on perceptions of brand authenticity and anticipated product quality. Specifically, studies 1 and 2 show that an intrinsic motivation increases authenticity perceptions which, in turn, increase perceived product quality, even for negatively regarded products. Studies 3a and 3b demonstrate that motivation affects perceived product quality (through perceived authenticity) by influencing deliberate attribute‐level inferences consumers make about the product, and Study 4 demonstrates that the positive effect of intrinsic motivation (through authenticity) disappears in the presence of objective product attribute information, when such inferences are no longer necessary. These findings suggest that authenticity perceptions are malleable, and they shed light on the mechanism through which brand authenticity leads consumers to anticipate that a brand's products will be higher in quality.